ISOLATION AND IDENTIFICATION OF CELLULOSE-DECOMPOSER FUNGUS PENICILLIUM OXALICUM AND DEHYDRATION EFFECTS OF ANALOG COMPOSTS - F. X. Zhu; Y. L. Yao; H. Z. Wei; C. L. Hong; L. F. Ping; Z. Y. Xue; X. Y. Chen; Y. K. Yang; W. P. Wang Z (Journal of Animal and Plant Sciences, 2015)
The aim of this study was to screen cellulose-decomposer microorganisms and to study the effects of dehydration in simulated composting. Cellulose-decomposer microorganisms were first isolated from fresh cow dung and cow dung natural compost in different stages by the cellulose-Congo Red medium. The obtained strains were further screened for a high ability to decompose cellulose by detecting the cellulose-enzyme activity and by observing the disintegration of filter paper and straw. A strong cellulose-decomposer microorganism was finally obtained and was identified as Penicillium oxalicum F12. The following aspects were experimentally determined to be the optimal conditions: a wheat bran and microcrystalline cellulose mix (4:1) as the carbon source, ammonium sulfate as the nitrogen source, pH of 5~6, 5% inoculum size, incubation at 30~35ºC for 120h. Under these conditions, the CMCase of strain F12 was 47.50 IU·mL- 1, and the FPA was 11.10 IU·mL-1. In a dehydration test of simulated composting, the water content of the inoculated processing residue material was decreased by 3.9% as compared with that of the control residue materials. The dehydration volume was 47.6g, which accounted for 19.8% of the initial material moisture content. Penicillium oxalicum F12 was a strong cellulose-decomposer microorganism with broad development potential.
Keywords: cellulose-decomposer microorganism; Penicillium oxalicum; simulated composting